2014
DOI: 10.4103/2141-9248.141496
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status, treatment needs and knowledge, attitude and practice of health care workers of Ambala, India - A cross-sectional study

Abstract: Background:Health care workers (HCWs) from an important component of the health care system of any nation. Adequate knowledge regarding oral health is also mandatory as it is directly related to general health. Aim: The present study was undertaken to assess oral health status and treatment needs of the health workers in Ambala district and to assess the knowledge, attitude and practices of HCWs.Subjects and Methods:A cross-sectional study was conducted among 148 HCWs of Ambala District. World Health Organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…This method is very specific and require a real understanding of different dental terms and how they look which might explain the low mean dental knowledge score for medical nurses in the current study. The unfavorable oral health behaviors reported in the present study among nurses is in agreement with previous studies which reported similar findings 14,19,20 . The favorable dental service utilization reported by nurses challenges the previous study by Oyetola et al 19 in which 98% of nurses reported unfavorable attendance pattern.…”
Section: Discussionsupporting
confidence: 93%
“…This method is very specific and require a real understanding of different dental terms and how they look which might explain the low mean dental knowledge score for medical nurses in the current study. The unfavorable oral health behaviors reported in the present study among nurses is in agreement with previous studies which reported similar findings 14,19,20 . The favorable dental service utilization reported by nurses challenges the previous study by Oyetola et al 19 in which 98% of nurses reported unfavorable attendance pattern.…”
Section: Discussionsupporting
confidence: 93%
“…(Marya, 2010) reported that the age group of 20-30 years high prevalence for periodontal disease (64.84%) whereas in the current study it was found to be the highest in of 35-49 years old (38.0%) which is contradicting and the possible reason could lack time for the oral care. Gambhir et al (2014) reported that the prevalence of early stages of PD involvement was 60.0%. The same author also quotes studies carried out in Trivandrum & Madras, which 90.3% and 95.0% respectively suffer from early stages of PD.…”
Section: Figure 5: the Frequencydistribution Of Periodontal Disease Among Urban And Rural Populationsmentioning
confidence: 99%
“…Dental caries and periodontal diseases are the most existing prevalent diseases throughout the world, especially in developing countries such as India. [ 4 - 6 ] “The prevalence of dental caries in Tamil Nadu was found to be 63.9%,”[ 7 ] and 50% of them had gingivitis, whereas 36% of the people in Tamil Nadu had a prevalence of periodontal diseases. [ 8 , 9 ] The Indian state of Tamil Nadu consists of 38 districts.…”
Section: Introductionmentioning
confidence: 99%